2005
DOI: 10.1152/ajpcell.00290.2004
|View full text |Cite
|
Sign up to set email alerts
|

MEK1 restores migration of polyamine-depleted cells by retention and activation of Rac1 in the cytoplasm

Abstract: Vaidya, Rajiv J., Ramesh M. Ray, and Leonard R. Johnson. MEK1 restores migration of polyamine-depleted cells by retention and activation of Rac1 in the cytoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 57 publications
4
25
0
Order By: Relevance
“…Injury-induced increases in the production of EGF and over-expression of the EGFR have been observed during mucosal repair [Tarnawski et al, 1992]. EGF activates MEK1, and we have shown that expression of CA-MEK1 restores migration in polyamine-depleted cells [Vaidya et al, 2005]. We have previously reported that maximal polyamine depletion occurs after 4 days of treatment with 5 mM DFMO [Ray et al, 2000].…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Injury-induced increases in the production of EGF and over-expression of the EGFR have been observed during mucosal repair [Tarnawski et al, 1992]. EGF activates MEK1, and we have shown that expression of CA-MEK1 restores migration in polyamine-depleted cells [Vaidya et al, 2005]. We have previously reported that maximal polyamine depletion occurs after 4 days of treatment with 5 mM DFMO [Ray et al, 2000].…”
Section: Discussionmentioning
confidence: 61%
“…Previous reports from our laboratory have shown that polyamine-depletion inhibited migration by preventing the activation of Rho family GTPases and subsequent cytoskeletal remodeling [McCormack et al, 1993;Ray et al, 2002]. We have also shown that sustained activation of MEK1 restored migration of polyamine-depleted cells by activating Rac1 to cause the reorganization of cortical actin into stress fibers [Vaidya et al, 2005]. Constitutively active (CA) MEK expressing cells migrated as solitary cells rather than as a monolayer sheet suggesting that MEK regulates the assembly and disassembly of adherens junctions.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations